2022
DOI: 10.1093/plcell/koac266
|View full text |Cite
|
Sign up to set email alerts
|

The localization of PHRAGMOPLAST ORIENTING KINESIN1 at the division site depends on the microtubule-binding proteins TANGLED1 and AUXIN-INDUCED IN ROOT CULTURES9 in Arabidopsis

Abstract: Proper plant growth and development requires spatial coordination of cell divisions. Two unrelated microtubule-binding proteins, TANGLED1 (TAN1) and AUXIN-INDUCED IN ROOT CULTURES9 (AIR9), are together required for normal growth and division-plane orientation in Arabidopsis (Arabidopsis thaliana). The tan1 air9 double mutant has synthetic growth and division-plane orientation defects while single mutants lack obvious defects. Here we show that the division site–localized protein, PHRAGMOPLAST ORIENTING KINESIN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We found that accumulation of TAN1-YFP at de novo cell plate insertion sites is partially dependent on the myosin XI O1. We hypothesized that since TAN1 interacts with PHRAGMOPLAST ORIENTING KINESIN1 (POK1) and POK2 (Müller, Han and Smith, 2006; Rasmussen, Sun and Smith, 2011; Mills, Morris and Rasmussen, 2022), and related kinesin 12s interact with myosin XI motor proteins including O1 (Huang et al ., 2022; Nan, Liang, et al ., 2023), O1 might be necessary for TAN1-YFP accumulation. TAN1-YFP fluorescence intensity during telophase was reduced but not absent in both correctly oriented and de novo cell plate fusion sites in o1 compared to wild-type siblings (Figure 4A-B, p = 1.02e-12, One-way ANOVA followed by Tukey’s HSD).…”
Section: Resultsmentioning
confidence: 99%
“…We found that accumulation of TAN1-YFP at de novo cell plate insertion sites is partially dependent on the myosin XI O1. We hypothesized that since TAN1 interacts with PHRAGMOPLAST ORIENTING KINESIN1 (POK1) and POK2 (Müller, Han and Smith, 2006; Rasmussen, Sun and Smith, 2011; Mills, Morris and Rasmussen, 2022), and related kinesin 12s interact with myosin XI motor proteins including O1 (Huang et al ., 2022; Nan, Liang, et al ., 2023), O1 might be necessary for TAN1-YFP accumulation. TAN1-YFP fluorescence intensity during telophase was reduced but not absent in both correctly oriented and de novo cell plate fusion sites in o1 compared to wild-type siblings (Figure 4A-B, p = 1.02e-12, One-way ANOVA followed by Tukey’s HSD).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of TAN1–YFP at de novo cell plate insertion sites is partially dependent on O1. Given that TAN1 interacts with PHRAGMOPLAST ORIENTING KINESIN1 (POK1) and POK2 ( Müller et al, 2006 ; Rasmussen et al, 2011 ; Mills et al, 2022 ), and related kinesin 12s interact with myosin XI motor proteins ( Huang et al, 2022 preprint; Nan et al, 2023 ), we hypothesized that O1 might be necessary for TAN1–YFP accumulation. TAN1–YFP fluorescence intensity during telophase was reduced but not absent in both correctly oriented and de novo cell plate fusion sites in o1 mutants compared to wild-type siblings [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…POK1 and POK2, which are plus end-directed kinesin-12 motor proteins that localize to the division site ( Lipka et al 2014 ; Chugh et al 2018 ; Herrmann et al 2018 ), might stabilize cortical-telophase microtubules. Since POK1 and POK2 directly interact with TAN1 ( Müller et al 2006 ; Rasmussen et al 2011 ; Lipka et al 2014 ; Mills et al 2022 ), they might also function together with TAN1 at the division site to capture microtubules. POK1 and POK2 may capture cortical-telophase microtubules at the division site just behind their plus ends and then move toward the plus ends, effectively pushing the minus ends away from the division site.…”
Section: Discussionmentioning
confidence: 99%